Fiber-reinforced stress reduced direct composites for endodontic treated tooth: a serial case report - Erwidawan, Mahar rosa; Satrio, Fajar; Rinastiti, Margareta; Enggardipta, Raras Ajeng (Jurnal Kedokteran Gigi Universitas Padjadjaran, 2025)
Introduction: Endodontically treated teeth (ETT) become more fragile due to the loss of tooth structural integrity as a result of caries, access preparation, decreased moisture content, and/or tooth fracture. These conditions influence the choice of restorative materials and techniques for ETT. Fiber-reinforced, stress-reduced direct composite (FR-SRDC) is a promising approach for restoring ETT because it preserves the remaining tooth structure and enhances fracture resistance. This case report evaluates the use of FR-SRDC in Class II cavities of ETT first maxillary molars with a six-month follow-up. Case Report: Case 1: A 35-year-old woman presented with a complaint of decay under an old filling placed two years ago in the left first maxillary molar, without pain on biting. Radiographic examination revealed a radiopaque filling on the mesio-occlusal surface and leakage marked by radiolucency between the restoration and the tooth structure extending toward the pulp. The diagnosis was pulp necrosis with asymptomatic apical periodontitis. The prognosis was good, considering the absence of pain and asymptomatic presentation. Case 2: A 29-year-old male complaining of decay in the left first maxillary molar and pain on biting for a week. The diagnosis was pulp necrosis with symptomatic apical periodontitis. The prognosis was fairly good, but required attention due to pain. Treatment for both cases consisted of root canal treatment (RCT) followed by restoration with FR-SRDC. The six-month follow-up showed good results for both cases, demonstrating the effectiveness and durability of fiber-reinforced, stress-reduced direct composite restorations. Conclusion: Fiber-reinforced, stress-reduced direct composites appear to be an effective restorative option for class II cavities in endodontically treated first maxillary molars, yielding favorable results over a six-month follow up period.Restorasi direk komposit dengan penguat fiber pada gigi pasca perawatan saluran akar: laporan kasus berserialPendahuluan: Gigi yang telah dirawat endodontik (ETT) menjadi lebih rapuh karena hilangnya integritas struktur gigi akibat karies, preparasi akses, berkurangnya kadar air, dan/atau fraktur gigi. Kondisi ini menentukan pilihan bahan dan teknik restorasi ETT. Komposit direk pengurangan stres yang diperkuat fiber (FR SRDC) adalah pendekatan yang baik untuk ETT karena akan mempertahankan struktur gigi yang tersisa dan meningkatkan ketahanan fraktur. Laporan kasus ini mengevaluasi penggunaan FR SRDC pada kavitas kelas II ETT molar pertama rahang atas dengan tindak lanjut 6 bulan. Laporan Kasus: Kasus 1: Wanita 35 tahun mengeluhkan kerusakan di bawah tambalan lama 2 tahun yang lalu pada molar pertama rahang atas kiri, tanpa rasa sakit saat menggigit. Pemeriksaan radiografi menunjukkan tambalan radiopak pada mesio-oklusal dan kebocoran tambalan yang ditandai dengan radiolusensi antara tambalan dan gigi hingga ke pulpa. Diagnosis: nekrosis pulpa, periodontitis apikal asimptomatik. Prognosis: Baik, mengingat tidak adanya rasa sakit dan kondisi asimptomatik. Kasus 2: Pria 29 tahun mengeluhkan kerusakan pada molar pertama rahang atas kiri dan rasa sakit saat menggigit selama seminggu. Diagnosis nekrosis pulpa, periodontitis apikal simptomatik. Prognosis cukup baik, namun memerlukan perhatian karena adanya rasa sakit. Indikasi perawatan untuk kedua kasus: Perawatan saluran akar (PSA) diikuti dengan FR SRDC. Tindak lanjut 6 bulan menunjukkan hasil yang baik untuk kedua kasus, mendemonstrasikan efektivitas komposit langsung pengurangan stres yang diperkuat serat. Simpulan: Komposit direk pengurangan stres yang diperkuat fiber dapat menjadi pilihan yang efektif pada kavitas kelas II gigi yang telah dirawat endodontik pada molar pertama rahang atas dengan hasil yang baik selama periode 6 bulan